Synthesis, cytotoxicity and apoptosis studies on nickel and zinc derivatives of testosterone-N4-substituted-thiosemicarbazones / Heng Mok Piew - Heng , Mok Piew (2020)
The side effects of cisplatin such as toxicities are mainly due to the lack of selectivity of this chemotherapeutic agent. In order to increase the selectivity of an anticancer agent, hormone molecule that targets a specific receptor may be utilized. This research aimed to prepare cytotoxic Schiff base compounds (and their nickel and zinc complexes) with testosterone and derivatives of thiosemicarbazide, which are potentially selective towards cancerous cells. Three Schiff base ligands (TM, TF, and TP) were made from the conjugation of testosterone with three derivatives of thiosemicarbazide (N4= methyl, fluorophenyl, and ethylphenyl) and their respective nickel (NM, NF, and NP) and zinc complexes (ZM, ZF, and ZP). A zinc complex ZE (N4= ethyl) was included as well. Characterizations of these compounds were done by means of FTIR, CHN elemental analyses, 1H-NMR and 13C-NMR, and X-ray crystallography. Mononuclear complexes of NM and NF adopt a distorted square planar geometry, with two molecules of Schiff base ligand coordinated to the nickel ion via two imine nitrogens and two tautomeric thiol sulfurs. The cytotoxicity of these compounds against several human cancerous cell lines (prostate cancer cell line PC-3 and LNCaP, breast cancer cell line MCF7, colorectal carcinoma cell line HCT 116) and their general toxicity against two human normal cell lines (normal prostate RWPE-1 and normal colon CCD-18Co) were investigated, with cisplatin as positive reference standard. Eight out of the nine synthesized compounds were cytotoxic towards the HCT 116 colorectal carcinoma cell line tested, while only two of them were toxic against the CCD-18Co normal colon cell line tested, reflecting high selectivity index of these compounds against the colorectal carcinoma cell line. Morphological changes induced by these compounds were observed and photographed. Ability of the cytotoxic compounds to induce apoptosis was proven via flow cytometry and this study was then focused on colorectal carcinoma cell line due to the high selectivity index. Five of the cytotoxic compounds (TM, NM, TF, TP, and NP) were able to depolarize the mitochondrial membrane potential, thereby suggesting their capability to induce intrinsic apoptotic pathways. All the cytotoxic compounds successfully arrested cell cycle of HCT 116 at G0/G1 phase. Furthermore, all the nine compounds were proven to bind to the DNA surface and they might be DNA minor groove binders. However, the general toxicity of TF against all the tested cell lines (IC50 values range from 12.03 to 29.37 μM) might be due to its outstanding affinity towards DNA (Kb = 2.9 × 107 M-1), while high selectivity of ZP (SI>3.22) might be due to its weak DNA binding strength (Kb = 3.7 × 105 M-1). The three compounds (TM, NM, and ZP) were able to suppress enzymatic reaction of topoisomerase I, thereby suggesting the cytotoxicity of these compounds against the colorectal carcinoma cell was due to their topo I inhibitory properties. Such inhibition might in turn, block the cell from entering S phase of cell cycle, and the cells might then be subjected to programmed cell death.